2015
DOI: 10.1007/s40279-015-0385-9
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Relationships of Resistance Training in Healthy Old Adults: A Systematic Review and Meta-Analysis

Abstract: BackgroundResistance training (RT) is an intervention frequently used to improve muscle strength and morphology in old age. However, evidence-based, dose–response relationships regarding specific RT variables (e.g., training period, frequency, intensity, volume) are unclear in healthy old adults.ObjectivesThe aims of this systematic review and meta-analysis were to determine the general effects of RT on measures of muscle strength and morphology and to provide dose–response relationships of RT variables throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
373
7
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(461 citation statements)
references
References 96 publications
(170 reference statements)
25
373
7
19
Order By: Relevance
“…We found that more repetitions of resistance exercise, but not number of sets, was associated with larger intervention effects. Other recent meta-analyses examining muscle strength outcomes with resistance training suggest that number of sets does not significantly impact strength gains among older adults (Borde, Hortobágyi, & Granacher, 2015; Silva, Oliveira, Fleck, Leon, & Farinatti, 2014). However, both meta-analyses examined studies with healthier samples.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that more repetitions of resistance exercise, but not number of sets, was associated with larger intervention effects. Other recent meta-analyses examining muscle strength outcomes with resistance training suggest that number of sets does not significantly impact strength gains among older adults (Borde, Hortobágyi, & Granacher, 2015; Silva, Oliveira, Fleck, Leon, & Farinatti, 2014). However, both meta-analyses examined studies with healthier samples.…”
Section: Discussionmentioning
confidence: 96%
“…Some meta-analyses focused only on frail populations (Chou et al, 2012; de Vries et al, 2012; Gine-Garriga et al, 2010) or only on cognitively impaired populations (Gates, Fiatarone Singh, Sachdev, & Valenzuela, 2013; Potter, Ellard, Rees, & Thorogood, 2011), while others excluded studies with participants with chronic illnesses common among older adults (Tschopp, Sattelmayer, & Hilfiker, 2011), limiting generalizability of study findings. Several prior meta-analyses restricted analyses to specific PF outcomes, such as balance (Howe et al, 2011; Orr, 2010), gait speed (Lopopolo et al, 2006), limb strength (Borde, Hortobágyi, & Granacher, 2015; Raymond, Bramley-Tzerefos, Jeffs, Winter, & Holland, 2013), or cardiorespiratory fitness (Lemura, von Duvillard, & Mookerjee, 2000). Additionally, two meta-analyses combined measures of PF with measures of disability (Gu & Conn, 2008; Liu & Latham, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Balance training for example, positively affects static/dynamic steady-state and proactive balance in older adults [6]. Likewise, resistance training has positive effects on measures of muscle strength [7] and balance [8] in older adults. Combinations of resistance and balance training describe in general a consecutive order, where resistance and balance exercises are executed within the same training session or within the same training block.…”
Section: Introductionmentioning
confidence: 99%
“…Undeniably, it is the skeletal muscle contractions and the activities that coincide with this type of stimulus that are of the high-intensity nature, which is predominantly neglected as we age. High-intensity exercise training, specifically "resistance-type exercise" training (RTET) that typically is conducted at intensities ≥ 70-85% of one repetition maximum, has been recommended for enhancing skeletal muscle mass and strength in healthy and older individuals [73][74][75][76]. While there may be exercise prescription concerns for individuals with specific risk factors and those with comorbidities, prescribing this mode of exercise and the overall execution of these high-intensity skeletal muscle contractions are not contraindications by themselves; however, medical and professional oversight is warranted and advised for aged populations, as is with all populations undergoing this type of resistance exercise training.…”
Section: Sscs As "Resistance-type Exercise" Training (Rtet)mentioning
confidence: 99%